Gender Homogeneity and Unidirectionality in Gender Role Reversal in Mathematics Textbook - Singh, Kavita (JOURNAL OF INDIAN EDUCATION, 2023)
Conventional wisdom regarded mathematics as a culture-free discipline. However, many researchers discarded this culture-free notion of mathematics, as the learning process of any discipline cannot be free from its social context. The process of teaching and learning mathematics may contain social influences and biases. As a result, it leaves math texts wide open to being tainted by the social construction of gender. Therefore, researchers felt the need to analyse mathematics textbooks through the gender lens and chose NCERT’s mathematics textbook of Class 6 (2020–21 edition) for content analysis. This paper presents the result of the analysis and discusses the newly emerged patterns of gender bias like gender homogeneity in groups and unidirectionality of gender role reversal in the textbook.